River basin governance enabling pathways for sustainable management: A comparative study between Australia, Brazil, China and France - Frederick Willem Bouckaert; Yongping Wei; James Pittock; Vitor Vasconcelos; Ray Ison (Ambio, 2022)
Successful river basin governance is challenged by actor engagement in the various stages of planning and management. A governance approach for determining priorities for actors for sustainable management was developed, based on a river basin diagnostic framework consisting of four social-institutional and four biophysical indicators. It was applied in river basins in Australia, Brazil, China and France. Actors diagnosed current and target capacity for these indicators, and estimated synergistic influences of interacting indicators. The results reveal different priorities and transformative pathways to achieve basin plan outcomes, specific to each basin and actor groups. Priorities include biodiversity for the Murray-Darling, local water management needs for the São Francisco and Yellow rivers, and improved decision-making for the Adour-Garonne. This novel approach challenges entrenched views about key issues and actor engagement roles in co-implementation of the basin plan under existing prevailing governance models, with implications for engagement and international collaboration on basin governance.

Governing in the Anthropocene: are there cyber-systemic antidotes to the malaise of modern governance? - Ray Ison; Jason Alexandra; Phil Wallis (Sustainability Science, 2018)

Watershed systems science—A new paradigm to understand and govern the impact of human activities on the earth’s surface in the Anthropocene - Ray Ison; YongPing Wei (Science China Earth Sciences, 2017)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Sustainable Catchment Managing in a Climate Changing World: New Integrative Modalities for Connecting Policy Makers, Scientists and Other Stakeholders - Ray Ison; Kevin Collins; John Colvin; Janice Jiggins; Pier Paolo Roggero; Giovanna Seddaiu; Patrick Steyaert; Marco Toderi; Chiara Zanolla (Water Resources Management, 2011)

Trusting Emergence: Some Experiences of Learning about Integrated Catchment Science with the Environment Agency of England and Wales - Kevin B. Collins; Ray L. Ison (Water Resources Management, 2010)